# 6s^2-13s+6=

## Simple and best practice solution for 6s^2-13s+6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6s^2-13s+6= equation:

Simplifying
6s2 + -13s + 6 = 0

Reorder the terms:
6 + -13s + 6s2 = 0

Solving
6 + -13s + 6s2 = 0

Solving for variable 's'.

Factor a trinomial.
(2 + -3s)(3 + -2s) = 0

#### Subproblem 1

Set the factor '(2 + -3s)' equal to zero and attempt to solve: Simplifying 2 + -3s = 0 Solving 2 + -3s = 0 Move all terms containing s to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3s = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3s = 0 + -2 -3s = 0 + -2 Combine like terms: 0 + -2 = -2 -3s = -2 Divide each side by '-3'. s = 0.6666666667 Simplifying s = 0.6666666667

#### Subproblem 2

Set the factor '(3 + -2s)' equal to zero and attempt to solve: Simplifying 3 + -2s = 0 Solving 3 + -2s = 0 Move all terms containing s to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2s = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2s = 0 + -3 -2s = 0 + -3 Combine like terms: 0 + -3 = -3 -2s = -3 Divide each side by '-2'. s = 1.5 Simplifying s = 1.5

#### Solution

s = {0.6666666667, 1.5}